Roadmap for advanced aqueous batteries: From design of materials to applications - Chao, Dongliang; Zhou, Wanhai; Xie, Fangxi; Ye, Chao; Li, Huan; Jaroniec, Mietek; Qiao, Shi-Zhang (Science advances, 2020)
Aqueous batteries are a reliable alternative for next-generation safe, low-cost, and scalable energy storage. Safety concerns about organic media-based batteries are the key public arguments against their widespread usage. Aqueous batteries (ABs), based on water which is environmentally benign, provide a promising alternative for safe, cost-effective, and scalable energy storage, with high power density and tolerance against mishandling. Research interests and achievements in ABs have surged globally in the past 5 years. However, their large-scale application is plagued by the limited output voltage and inadequate energy density. We present the challenges in AB fundamental research, focusing on the design of advanced materials and practical applications of whole devices. Potential interactions of the challenges in different AB systems are established. A critical appraisal of recent advances in ABs is presented for addressing the key issues, with special emphasis on the connection between advanced materials and emerging electrochemistry. Last, we provide a roadmap starting with material design and ending with the commercialization of next-generation reliable ABs.